Question and Answers Forum

All Questions      Topic List

Differentiation Questions

Previous in All Question      Next in All Question      

Previous in Differentiation      Next in Differentiation      

Question Number 165581 by mnjuly1970 last updated on 04/Feb/22

  ϕ(t)=∫_0 ^( (π/2)) ( sin(x)+t cos(x))^( 2) dx  find  the  value of the extermum                 of   ϕ (t).

φ(t)=0π2(sin(x)+tcos(x))2dxfindthevalueoftheextermumofφ(t).

Answered by aleks041103 last updated on 04/Feb/22

sin(x)+tcos(x)=(√(1+t^2 ))sin(x+arctan(t))  ⇒ϕ(t)=∫_0 ^(π/2) ((sin^2 (x+a))/(1+t^2 ))dx=  =(1+t^2 )∫_a ^(a+π/2) sin^2 x dx , a=tan^(−1) t  ∫sin^2 x dx= ∫((1−cos(2x))/2)dx=  =(x/2)−(1/4)sin(2x)  ⇒∫_a ^(a+π/2) sin^2 x dx=(π/4)−(1/4)(sin(π+2a)−sin(2a))=  =(π/4)+sin(a)cos(a)=  =(π/4)+tan(a)cos^2 (a)=  =(π/4)+(t/(1+tan^2 (a)))=(π/4)+(t/(1+t^2 ))  ⇒ϕ(t)=(π/4)(1+t^2 )+t

sin(x)+tcos(x)=1+t2sin(x+arctan(t))φ(t)=0π/2sin2(x+a)1+t2dx==(1+t2)aa+π/2sin2xdx,a=tan1tsin2xdx=1cos(2x)2dx==x214sin(2x)aa+π/2sin2xdx=π414(sin(π+2a)sin(2a))==π4+sin(a)cos(a)==π4+tan(a)cos2(a)==π4+t1+tan2(a)=π4+t1+t2φ(t)=π4(1+t2)+t

Commented by aleks041103 last updated on 04/Feb/22

ϕ(t)=(π/4)t^2 +t+(π/4)  ϕ′=(π/2)t+1=0  ⇒t=−(2/π)  ⇒ϕ_(extr) =(π/4) (4/π^2 )−(2/π)+(π/4)=  =−(1/π)+(π/4)=((π^2 −4)/(4π))=ϕ_(extr.)

φ(t)=π4t2+t+π4φ=π2t+1=0t=2πφextr=π44π22π+π4==1π+π4=π244π=φextr.

Answered by mahdipoor last updated on 05/Feb/22

ϕ^′ (t)=lim_(k→t) ((ϕ(k)−ϕ(t))/(x−t))=  lim_(k→t) ((∫_0 ^( π/2) (k^2 −t^2 )cos^2 x+2(k−t)sinx.cosx)/(k−t))=  lim_(k→t) ∫_0 ^( π/2) (k+t)cos^2 x+2sinx.cosx =  2t∫_0 ^( π/2) cos^2 x +∫_0 ^( π/2) 2sinx.cosx=(π/2)t+1  ⇒ ϕ^′ (t)=0 ⇒ t=−(2/π)  ⇒ϕ(t)=∫ϕ^′ (t).dt=(π/4)t^2 +t+c  ⇒ϕ(0)=∫_0 ^( π/2) (sinx)^2 =(π/4) ⇒c=(π/4)  min ϕ = ϕ(−(2/π))=((π^2 −4)/(4π))

φ(t)=limktφ(k)φ(t)xt=limkt0π/2(k2t2)cos2x+2(kt)sinx.cosxkt=limkt0π/2(k+t)cos2x+2sinx.cosx=2t0π/2cos2x+0π/22sinx.cosx=π2t+1φ(t)=0t=2πφ(t)=φ(t).dt=π4t2+t+cφ(0)=0π/2(sinx)2=π4c=π4minφ=φ(2π)=π244π

Commented by aleks041103 last updated on 04/Feb/22

On the second line:  ((∫_0 ^( π/2) [(k^2 −t^2 )cos^2 x+2(k−t)sinx.cosx]dx)/(k−t))  since  ϕ(t)=∫_0 ^(π/2) (sin(x)+t cos(x))^2 dx

Onthesecondline:0π/2[(k2t2)cos2x+2(kt)sinx.cosx]dxktsinceφ(t)=0π/2(sin(x)+tcos(x))2dx

Commented by mahdipoor last updated on 04/Feb/22

thanks for your hint

thanksforyourhint

Commented by mahdipoor last updated on 05/Feb/22

bozorgvari aziz

bozorgvariaziz

Commented by mnjuly1970 last updated on 04/Feb/22

        ali bood jenabe mahdipoor.  mamnoon.

aliboodjenabemahdipoor.mamnoon.

Terms of Service

Privacy Policy

Contact: info@tinkutara.com